Mediation with a puppet: The effects on teachers' mediated learning strategies with children in special education and regular kindergartens. (December 2018) - Tzuriel, David; Remer, Ronit
Abstract: The main objectives of this study were to investigate the effects of mediation with a puppet on teachers' mediated learning experience (MLE) strategies. The sample was composed of 18 teachers and 145 kindergarten children, selected from special education (n = 68) and regular (n = 77) kindergartens. About half of each group was assigned to a puppet and half to a no-puppet group. Each teacher was assigned to a small group of 3–5 children and asked to teach them a story for 15 min in a puppet and 15 min in no-puppet conditions in a counterbalanced order. The teaching lessons were videotaped and analyzed by the Observation of Mediation Interaction scale. The findings revealed that teachers in the puppet condition used significantly and uniquely higher levels of mediation in all MLE strategies than in the no-puppet condition. A significant Mediation Modality X MLE Strategy interaction indicates that the differences between the two conditions were highest in strategies of Intentionality and Reciprocity and Meaning and lower in strategies of Transcendence, Feelings of Competence and Self-Regulation. Use of a puppet was effective similarly for children in special education as for children in regular group. When mediators accessed the puppet (i.e., in puppet condition) their level of mediation for Meaning was significantly higher than when the puppet was not accessed. When mediators did not access the puppet their level of mediation for Intentionality and Reciprocity, Feelings of Competence, and Self-Regulation was higher than when the puppet was accessed. The findings were discussed in relation to MLE theory and educational implications are provided. Highlights: Teaching with a puppet elicits higher level of mediation strategies than teaching without a puppet. Highest differences between puppet and no puppet conditions were in Intentionality and Reciprocity and Meaning. Use of a puppet was effective similarly for children in special education as for children in regular group. When the puppet was accessed, in puppet condition, mediation for Meaning was significantly higher than when the puppet was not accessed.